On the structure of excited states of nuclei 4He, 6He and 6Li from the 3H(α, tt)p and 3H(α, τt)n reactions - O. M. Povoroznyk; O. K. Gorpinich; G. V. Mokhnach; O. A. Ponkratenko; O. O. Jachmenjov (Ядерна фізика та енергетика)
Analysis of the spectra t-t and t-t coincidences obtained for different pairs of registration angles t-particles and tritons in the kinematically complete study of three-particle 3H(a, tt)p and 3H(a, tt)n nuclear reactions at energies of alpha particles 67,2 MeV was performed. Experimentally, higher than the correspond thresholds of decay a single state with t + t structure of 6He (E* » 18,3 MeV), and the doublet structure t + t in the 6Li (E*» 21,59 MeV and E* » 21,9 MeV) was observed. At the same time energy positions and widths of 2 - 4 excited states of 4He and the ratios of their decay modes through t + p and t + n were determined.